AMERICAN ACCOUNTING - Mihaela Onica (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2005)
The international Accounting Standards already contribute to the generation of better and more easily comparable financial information on an international level, supporting thus a more effective allocationof the investments resources in the world. Under the circumstances, there occurs the necessity of a consistent application of the standards on a global level. The financial statements are part of thefinancial reporting process. A set of complete financial statements usually includes a balance sheet,a profit and loss account, a report of the financial item change (which can be presented in various ways, for example as a status of the treasury flows and of the funds flows ) and those notes, as well as those explanatory situations and materials which are part of the financial statements.